1997
DOI: 10.1002/(sici)1096-8628(19971212)73:2<144::aid-ajmg8>3.0.co;2-u
|View full text |Cite
|
Sign up to set email alerts
|

Severe brain and limb defects with possible autosomal recessive inheritance: A series of six cases and review of the literature

Abstract: Six fetuses with normal chromosomes were found to have severe craniofacial, limb, and visceral malformations during the second trimester of pregnancy. Two of these fetuses were monozygotic twins while a third one had a healthy dizygotic twin brother. A case with familial recurrence was also observed. Autopsy and skeletal radiographs suggested several diagnoses such as neural tube defect with limb defects or XK aprosencephaly. The development of these severe conditions in monozygotic twins and familial recurren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Aprosencephaly/atelencephaly is etiologically heterogeneous. It occurs sporadically for the most part, but is also found in the XK‐aprosencephaly syndrome (Renzetti et al,2005); in aneuploidy syndromes, such as del(13q) (Towfighi et al,1987) or r(13) mosaicism (Goldsmith et al,1993); and as a familial, presumably autosomal recessive trait (Townes et al,1988; Florell et al,1996; Labrune et al,1997). Renzetti et al (2005) reported XK‐aprosencephaly in 2 sibs of North African origin.…”
Section: Central Nervous Systemmentioning
confidence: 99%
“…Aprosencephaly/atelencephaly is etiologically heterogeneous. It occurs sporadically for the most part, but is also found in the XK‐aprosencephaly syndrome (Renzetti et al,2005); in aneuploidy syndromes, such as del(13q) (Towfighi et al,1987) or r(13) mosaicism (Goldsmith et al,1993); and as a familial, presumably autosomal recessive trait (Townes et al,1988; Florell et al,1996; Labrune et al,1997). Renzetti et al (2005) reported XK‐aprosencephaly in 2 sibs of North African origin.…”
Section: Central Nervous Systemmentioning
confidence: 99%
“…(1988) described a sibship in which there were twins with anencephaly and a female infant with aprosencephaly, fused humerus and radius, and oligodactyly, and suggested that XK aprosencephaly syndrome may be an autosomal recessive disorder. Labrune et al. (1997) described six fetuses with normal chromosomes and severe craniofacial, limb, and visceral malformations observed during the second trimester of pregnancy.…”
Section: Introductionmentioning
confidence: 99%